The evolution of the kinematic analysis to obtain the distance covered by basketball players. - Panhan, Ana Carolina; Maia, Juliana Landolfi; Monezi, Lucas Antônio; Misuta, Milton Shoiti; Mercadante, Luciano Allegretti (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The methods used to evaluate the distances covered by basketball players change much over time. With technological and computational advances, now you can perform the tracking of the players in real game situation, without interfering with the performance, or the rules of the sport. Objectives: To conduct a literature review of the findings related to distances covered by male basketball players being in competition situation or not and their methodologies used to obtain the results. Methods: A literature review (GOOGLE SCHOLAR and LILACS) was performed to collect articles about the results of the distances covered by elite basketball players and sub-elite, male, tests or competitions and the methodologies used to obtain these results. Results: According to the literature the methodologies used can be divided in three parts: a) methodologies for subjective direct observation of the games; b) observation from filming; c) Tracking players in image sequences. Four papers were found to direct observation methodology games, four works for observation methodology from filming and five papers for players tracking methodology from filming, totaling 13 projects, 11 articles, a dissertation and a monograph. Conclusion: The methods used have allowed the determination of distances accurately and analysis could differentiate the players and functions in different cases, with several factors involved. The distance covered is very important for physical and technical trainers basketball teams to standardize and periodization of training of athletes and individual or collective, and to improve the performance of the players during the games.